Evaluating blockchain adoption barriers in China’s IP trade and protection internationally - Li, Qiang; Wen, XiaoLong; Wu, Zijing (Frontiers in Blockchain, 2025)
BackgroundBlockchain technology offers transformative potential for international intellectual property (IP) trade and protection, yet its adoption in China faces significant barriers.MethodThis study utilizes the Analytic Hierarchy Process (AHP) to quantitatively prioritize regulatory, technological, economic, and sociocultural barriers, drawing on data from expert interviews.FindingsThe analysis identifies regulatory barriers, particularly compliance costs (weight: 0.308) and data security regulations (0.168), as the primary challenges, largely due to stringent regulations such as China’s Cybersecurity Law. Technological barriers, including infrastructure limitations (0.198) and high implementation costs (0.132), are also significant. Economic and sociocultural barriers, such as awareness gaps and trust deficits, are less critical but still relevant. Addressing these challenges requires collaboration among policymakers, technology providers, and IP stakeholders.ConclusionThis research offers actionable insights for advancing blockchain integration in China’s IP ecosystem. Future studies should expand sample sizes and explore alternative decision-making frameworks to improve generalizability.